Effect of Deep Cervical Flexor Training on Craniovertebral Angle and Muscle Endurance among Students with Forwarding Head Posture - Jamaica Manlogon; Maurice Villafranca (Philippine Association of Institutions for Research, Inc., 2019)
With the ease of use and a wide variety of choices of smartphones, it significantly affects the ways of life in terms of socializing, applications, gathering, and sharing information. Little do people know that it can also affect posture. This is where an introduction of exercise that targets the muscles involved in the impaired posture comes to maintain a proper posture. This study aimed to evaluate the effect of deep cervical flexor training on the craniovertebral angle and muscle endurance of students with forwarding head posture. The study is an experimental type of research that was utilized on thirty (30) junior high school students who had undergone fishbowl technique selection and were assigned to two (2) groups namely control and experimental group. Craniovertebral angle and deep neck flexor endurance test were used to determine the pre-and post-test of both groups. There is a significant difference in the paired t-test result of the pre-and post-test outcome of deep cervical flexor training of the experimental group in terms of CVA. In contrast to DNFET, there is no significant difference in the paired t-test result of the pre-and post-test intervention of deep cervical flexor training of the experimental group. Deep cervical flexor training is useful to increase CVA.